Closed-loop force control for haptics simulation Sensory-Mode Interaction - Shoon So Oo, Shoon (Universiti Teknologi Petronas, 2009)
I laptics is the science of touch. The project is based on the concept of sensorymode interaction, haptics simulation and closed-loop force control feedback. Three different types of objects with three different stiffness and friction are simulated and touched via PHANToM device. In order to control and prevent the permenant deformation of materials, the input force that user exert while touching the virtual object should be control. The simulation program also controls the user input force according to the maximum force that each materials can accept. After the simulation program was completed, a simple controller will designed for the system and performances will be analyzed. This report explains in details about how to implement haptic program, controlling the user input force in accordance with real life data as well as the plans to implement the controller for the haptic simulation system completed.